PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN SOCIAL MEDIA MARKETING TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN PADA PELANGGAN PONDOK IKAN BAKAR SASMITA DI PASIR PENGARAIAN - Sasmita Sasmita; Musfar Firli Tengku; Taufiqurrahman Taufiqurrahman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of product quality, service quality and social media marketing on customer loyalty and customer satisfaction at the Sasmita Grilled Fish Cottage customers in Pasir Pengaraian. The population in this study were all customers of Pondok Ikan Bakar Sasmita. Primary data were collected using a questionnaire as an instrument to see the results of the study, to test the hypothesis in this study using path analysis (path analysis) with the help of the SPSS program. The sampling technique chosen was purposive sampling method with a total sample of 80 customers of Pondok Ikan Bakar Sasmita. The results show that: 1) product quality has a significant effect on customer satisfaction at Pondok Ikan Bakar Sasmita, 2) service quality has a significant effect on customer satisfaction at Pondok Ikan Bakar Sasmita, 3) social media marketing has a significant effect on customer satisfaction at Pondok Ikan Bakar Sasmita, 4) customer satisfaction has a significant effect on customer loyalty at Pondok Ikan Bakar Sasmita, 5) product quality has a significant effect on customer loyalty at Pondok Ikan Bakar Sasmita, 6) service quality has a significant effect on customer loyalty at Pondok Ikan Bakar Sasmita, 7) social media marketing has a significant effect on customer loyalty Sasmita Grilled Fish Cottage. Keywords: product quality, service quality, social media marketing, customer satisfaction, customer loyalty